Durable Benefits of Cellular Postconditioning: Long‐Term Effects of Allogeneic Cardiosphere‐Derived Cells Infused After Reperfusion in Pigs with Acute Myocardial Infarction. Issue 2 (8th February 2016) - Kanazawa, Hideaki; Tseliou, Eleni; Dawkins, James F.; De Couto, Geoffrey; Gallet, Romain; Malliaras, Konstantinos; Yee, Kristine; Kreke, Michelle; Valle, Ileana; Smith, Rachel R.; Middleton, Ryan C.; Ho, Chak‐Sum; et al.
Abstract : Background: Infusion of allogeneic cardiosphere‐derived cells (allo‐CDCs) postreperfusion elicits cardioprotective cellular postconditioning in pigs with acute myocardial infarction. However, the long‐term effects of allo‐CDCs have not been assessed. We performed a placebo‐controlled pivotal study for long‐term evaluation, as well as shorter‐term mechanistic studies. Methods and Results: Minipigs underwent 1.5‐hour mid‐left anterior descending balloon occlusion followed by reperfusion and were randomized to receive intracoronary allo‐CDCs or vehicle 30 minutes postreperfusion. Left ventriculography (LVG) demonstrated preserved ejection fraction (EF) and attenuation of LV remodeling in CDC‐treated pigs. Pigs underwent cardiac magnetic resonance imaging (MRI) and LVG 1 hour and 8 weeks after therapy to evaluate efficacy. MRI showed improvement of EF and attenuation of LV remodeling immediately after allo‐CDC infusion. In addition, allo‐CDCs improved regional function and decreased hypertrophy 2 months post‐treatment. Histological analysis revealed increased myocardial salvage index, enhanced vascularity, sustained reductions in infarct size/area at risk and scar transmurality, and attenuation of collagen deposition in the infarct zone of allo‐CDC‐treated pigs at 2 months. Allo‐CDCs did not evoke lymphohistiocytic infiltration or systemic humoral memory response. Short‐term experiments designed to probe mechanism revealed antiapoptotic effects of allo‐CDCs on cardiomyocytes and increases in cytoprotective macrophages, but no increase in overall inflammatory cell infiltration 2 hours after cell therapy. Conclusions: Allo‐CDC infusion postreperfusion is safe, improves cardiac function, and attenuates scar size and remodeling. The favorable effects persist for at least 2 months after therapy. Thus, cellular postconditioning confers not only acute cardioprotection, but also lasting structural and functional benefits.